Effect of substrate on metabolite production of Alternaria alternata. - Burroughs, R (1976)
Alternariol and alternariol monomethyl ether are commonly associated with weathered grain sorghum. Production of these metabolites and altenuene by isolates of Alternaria alternata was evaluated on various sterile grain substrates. At 35% moisture content and 25 C, metabolite yields were highest on rice, intermediate on sorghums, and lowest on wheat and yellow corn. Fourteen-to 21-day cultures on milled rice were best in terms of ease of metabolite recovery, even though yields were higher on 28-day cultures of rough and brown rice. Metabolite production was reduced when rice was supplemented with yeast extract or yeast extract plus Czapek-Dox broth.